TRANSAKSI JUAL BELI DROPSHIPPING DALAM PERSPEKTIF FIQH MUAMALAH - Bariroh, Muflihatul (IAIN Tulungagung, 2016)
One of transaction trading online systems that are currently beingpopular among the community is the trading with the dropshippingsystem. This system involves three parties namely supplier, dropshipperand consumers .The dropshipper does not require to possess the itemsbeing sold , but only provide sales for marketing goods through thewebsite and social media .The system of such trading in practicecauses several problems in Islamic law because the dropshipperssell goods which is not in their possession .This study aims toexplain dropshipping trading system and review its practices fromthe perspective of Islamic law or Fiqh. This study employs a libraryresearch method. The results indicate that the practice of dropshippingtrading online is not against Islamic law although the dropshippers donot possess the goods offered to the consumers. Such trading systemis allowed to use wakalah agreement, hail and samsarah. It shouldbe noted that the dropshippers must also be honest and present trueinformation regarding the condition and the specification of the goodsbeing traded.Kata kunci: Dropshipping, Dropshipper, Salam, Samsarah, Wakalah